FACTORS DETERMINING THE HOSPITALISATION DURATION OF STAY IN CHILDREN WITH SEVERE RESPIRATORY SYNCYTIAL VIRUS (RSV) INFECTION IN THE RUSSIAN FEDERATION - A.A. Baranov; L.S. Namazova-Baranova; T.V. Kulichenko; M.D. Bakradze; E.A. Degtyareva; L.M. Ogorodova; K.L. Gooch; K.M. Gudkov; G. Notario; H. Khong; K. Buesch; V.K. Tatochenko (Педиатрическая фармакология)
The epidemiologic data on RSV infection prevalence in the Russian Federation and its impact on respiratory morbidity in the pediatric population are limited. This article provides the analysis of results of a prospective, multicenter, observational cohort study. The study was conducted in 9 centers in the Russian Federation — in Moscow, St. Petersburg, and Tomsk. Children less than 2 years of age were included. It was found that during the season of high RSV morbidity RSV is found in 38 % of children hospitalized for lower respiratory tract infections; mean hospitalisation duration in children with severe RSV infection was over 1 week. Usually the duration of hospitalization was associated with disease severity and requirements for healthcare resources and oxygen supplementation. Moreover, in the Russian Federation the hospital length of stay in patients with RSV infection depended on the type of medical insurance. It was demonstrated that RSV infection caused severe respiratory failure in some infants less than 1 year of age and, therefore, was a substantial burden for the system of hospital medical care in the Russian Federation. Prophylaxis of severe RSV infection in high-risk groups of children during the might reduce the need for hospitalization. Key words: respiratory syncytial virus infection, bronchiolitis, risk factors, prophylaxis, epidemiology, children. (Pediatric pharmacology. — 2011; 8 (6): 61–66).